Utilization of wood sawdust as pore-forming agent for clay-based porous ceramic - Afiqah Awang Kechik (2024)
Porous ceramics have a high percentage of porosity ranging from 20% to 95% and are suitable for applications such as thermal insulators and lightweight bricks. Porous ceramic is usually made from clay and a pore-forming agent (PFA). Currently, the PFA used is synthetic chemicals such as oil shale (OS), expandable polystyrene (EPS), carbon, polymer microbeads, and tert-butyl alcohol (TBA), which are toxic and hazardous to human health. Hence, utilization of natural PFA, especially from natural solid waste, is seen as a greener option to reduce the dependency on synthetic chemicals. PFA is added to a material to create pores in it. These pores can make the material lighter and improve insulative property. To the best of our knowledge, only few researchers have proposed utilizing wood sawdust (WSD) as PFA for porous ceramic. WSD has a a fine and uniform particle size distribution (1.5 μm to 63 μm), thus suitable as PFA for porous ceramic. WSD also has a much lower ignition point of approximately 118 °C to 142 °C. Hence, a much lower sintering temperature can be applied to ignite the WSD and eventually form pores during sintering. Therefore, this study aims to investigate the suitability of WSD in terms of weight percentage (10 – 40 wt.%) and sintering temperature (900°C - 1100°C) influence porous ceramic using General Full Factorial Statistical Design (GFFSD). GFFSD statistically proved that wt.% of WSD and sintering temperature significantly influence the physical (water absorption, apparent porosity, and bulk density) and mechanical (compressive strength) properties of porous ceramic. As the wt.% of WSD increased, porous ceramic's water absorption and apparent porosity increased. Subsequently, the bulk density and compressive strength decreased. Besides, the increment of sintering temperature at each wt.% of WSD decreased the water absorption and apparent porosity. Meanwhile, the bulk density and compressive strength increased. From XRD and SEM analysis, it was found that factors such as mullite (Al6Si2O13), wollastonite (CaSiO3), and grossite (CaAl4O7) crystalline phases, pores distribution, and micro-cracking affect the physical and mechanical properties of the porous ceramic. A good balance of porosity and compressive strength was found in the porous ceramic with 10 wt.% of WSD, sintered at 1100 °C. This combination provides a perfect balance of adequate porosity and compressive strength. In essence, the material balances the right amount of porosity and strength. Therefore, the wood sawdust has great potential to be used as a thermal insulator and light-weight brick.